Exploring the role of innate lymphoid cells in the periodontium: insights into immunological dynamics during orthodontic tooth movement - Pastille, Eva; Konermann, Anna (Frontiers in Immunology, 2024)
Background The periodontal ligament (PDL) experiences considerable mechanical stresses between teeth and bone, vital for tissue adaptation, especially in orthodontic tooth movement (OTM). While recent research emphasizes the role of innate lymphoid cells (ILCs) in regulating sterile inflammation, their involvement in periodontal tissues during OTM remains largely unexplored. Methods In this study, PDL tissues from orthodontic patients (n = 8) were examined using flow cytometry to detect ILC subtypes. Transwell co-culture systems were used to expose PDL cells to mechanical strain, followed by measuring migration and ratios of sorted ILC subtypes. Statistical analyses were conducted using paired Student’s t-test, Kruskal-Wallis test, Dunn’s post-test and one-way/two-way ANOVA with Tukey’s post-test (p≤ 0.05; **, p≤ 0.01; ***, p≤ 0.001). Results Our findings demonstrate a significant increase in CD127+ CD161+ ILC frequencies in PDL tissues during OTM, indicating ILC involvement in sterile inflammation induced by orthodontic forces. Co-culture assays show directed migration of ILC subsets towards PDL cells and substantial proliferation and expansion of ILCs. Conclusions This study is the first to comprehensively investigate the role of ILCs in sterile inflammation during OTM, revealing their presence and distribution within PDL tissues’ innate immune response in vivo, and exploring their migratory and proliferative behavior in vitro. The results suggest a crosstalk between ILCs and PDL cells, potentially influencing the inflammatory response and tissue remodeling processes associated with OTM.